2001
DOI: 10.1128/jcm.39.6.2348-2350.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibilities, Varieties, and Electrophoretic Karyotypes of Clinical Isolates of Cryptococcus neoformans from Brazil, Chile, and Venezuela

Abstract: One hundred clinical isolates of Cryptococcus neoformans from human immunodeficiency virus (HIV)-infected and non-HIV-infected patients from Brazil, Chile, and Venezuela were separated according to varieties and tested for antifungal susceptibility. A high susceptibility to antifungal agents was observed among all the isolates. The electrophoretic karyotyping of 51 strains revealed good discrimination among Cryptococcus neoformans var. neoformans strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
38
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 10 publications
9
38
1
2
Order By: Relevance
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009). This divergence in results may be due to a possible lack of uniformity in the methodologies of testing adopted by different investigators.…”
Section: Discussionsupporting
confidence: 54%
“…grubii, which agrees with several previous reports (Fernandes et al, 2003;Trilles et al, 2004;Khan et al, 2007Khan et al, , 2009Gomez-Lopez et al, 2008). However, there is divergence of results concerning the antifungal susceptibility patterns of the two species in some other studies, which reported no such difference (Chen et al, 2000;Calvo et al, 2001;Morgan et al, 2006;Tay et al, 2006;Thompson et al, 2009). This divergence in results may be due to a possible lack of uniformity in the methodologies of testing adopted by different investigators.…”
Section: Discussionsupporting
confidence: 54%
“…Several molecular typing methods have been used in epidemiological analyses of clinical and/or environmental isolates of C. neoformans, including karyotyping, PCR fingerprinting, random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP) 5,7,8,10,12,16,22,26,37,45 . PCR-fingerprinting using mini (M13) or microsatellite [(GACA) 4 ] specific sequences as single primers and RFLP (PLB1 and URA5 genes) methods have grouped global isolates of C. neoformans into eight major molecular types 32,37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcosis is the second most important fungal disease in human immunodeficiency virus (HIV)-positive patients, where disseminated infection is commonly fatal (Ito-Kuwa et al 1994, Pinner et al 1995, Patterson 1997, Calvo et al 2001. In Brazil 4.5% of all opportunistic infections in AIDS patients have been reported as being caused by Cryptococcus neoformans (Ministério da Saúde 1999).…”
mentioning
confidence: 99%